Archaeology essentials theories, methods, and practice - Renfrew, Colin 1937-; Bahn, Paul G. (New York Thames & Hudson, 2008)
A guide to all aspects of archaeology, this work provides a readable and compact introduction to archaeology for those new to the field. Long-established techniques are carefully explained as well as exciting new methods as the authors describe the ways in which archaeologists seek to explain and interpret the remote past of humankind.
Keywords: Archaeology -- Textbooks